Clinical and epidemiological profile of patients with early stage mycosis fungoides - Gustavo Moreira Amorim; João Paulo Niemeyer-Corbellini; Danielle Carvalho Quintella; Tullia Cuzzi; Márcia Ramos- (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Mycosis fungoides is the most common form of primary cutaneous lymphoma, with an indolent, slowly progressive course and 88% five-year survival rate. The diagnosis is challenging, especially in the early stages, and usually relies on a good clinical-histopathological correlation. Objective: The aim was to establish the clinical and epidemiological profile of patients with early-stage mycosis fungoides. Methods: This was a retrospective cross-sectional observational study with an exploratory analysis. Outcome variables were disease progression and mycosis fungoides-related death. Results: One hundred and two patients were included. The majority were white males, with a mean age of 55.6 years. Mean time from onset of lesions to diagnosis was 51.08 months. The majority of patients were classified as IB stage according to TNMB. Mean follow-up time was 7.85 years. Disease progression was seen in 29.4% of the patients. Death related to the disease occurred in 7.9% of patients. Plaque lesions, involvement of more than 10% of the body surface, altered lactate dehydrogenase and beta-2-microglobulin, and stage IB were significantly associated with disease progression, and altered lactate dehydrogenase and beta-2-microglobulin also correlated with higher frequency of deaths. Study limitations: Small sample and retrospective design. Conclusions: The clinical and epidemiological profile of patients with early-stage mycosis fungoides in our sample corroborates reports in the literature. Diagnostic delay in our series is also consistent with previous findings, but the rate of disease progression, despite treatment, was higher than reported in the literature.